Who contributes? A strategic approach to a European immigration policy - Giuseppe Russo; Luigi Senatore (IZA Journal of Migration, 2013)
Who pays for immigration control? According to the Lisbon Treaty the cost of enforcing the European border against illegal immigration shall be shared among the EU members. Nonetheless, the Treaty is vague with respect to the 'appropriate measures' to adopt in order to distribute the financial burden. Members who do not share their borders with source countries have an incentive to free ride on the other countries. We study a novel contribution game in which a border country and a central country minimize a loss function with respect to their national immigration target. We consider both sequential and simultaneous decisions and we show that joint contribution occurs only if the immigration targets are not too different. Total contribution is higher in the simultaneous game, but the sequential framework reduces the incentive to free ride.
Keywords: D78; H72; H77; 330; policy making; government expenditures; local government expenditures; federalism; programme evaluation; duration analysis; timing-of-events model